ASP with non-herbrand partial functions: a language and system for practical use - BALDUCCINI, MARCELLO (Theory and practice of logic programming, 2013)
Dealing with domains involving substantial quantitative information in Answer Set Programming (ASP) often results in cumbersome and inefficient encodings. Hybrid “CASP” languages combining ASP and Constraint Programming aim to overcome this limitation, but also impose inconvenient constraints – first and foremost that quantitative information must be encoded by means of total functions. This goes against central knowledge representation principles that contribute to the power of ASP, and makes the formalization of certain domains difficult. ASPf is being developed with the ultimate goal of providing scientists and practitioners with an alternative to CASP languages that allows for the efficient representation of qualitative and quantitative information in ASP without restricting one's ability to deal with incompleteness or uncertainty. In this paper we present the latest outcome of such research: versions of the language and of the supporting system that allow for practical, industrial-size use and scalability. The applicability of ASPf is demonstrated by a case study on an actual industrial application.